Ambient Fabrication of Organic–Inorganic Hybrid Perovskite Solar Cells. Issue 1 (18th September 2020) - Zhang, Yuan; Kirs, Ashleigh; Ambroz, Filip; Lin, Chieh‐Ting; Bati, Abdulaziz S. R.; Parkin, Ivan P.; Shapter, Joseph G.; Batmunkh, Munkhbayar; Macdonald, Thomas J.
Abstract: Organic–inorganic hybrid perovskite solar cells (PSCs) have attracted significant attention in recent years due to their high‐power conversion efficiency, simple fabrication, and low material cost. However, due to their high sensitivity to moisture and oxygen, high efficiency PSCs are mainly constructed in an inert environment. This has led to significant concerns associated with the long‐term stability and manufacturing costs, which are some of the major limitations for the commercialization of this cutting‐edge technology. Over the past few years, excellent progress in fabricating PSCs in ambient conditions has been made. These advancements have drawn considerable research interest in the photovoltaic community and shown great promise for the successful commercialization of efficient and stable PSCs. In this review, after providing an overview to the influence of an ambient fabrication environment on perovskite films, recent advances in fabricating efficient and stable PSCs in ambient conditions are discussed. Along with discussing the underlying challenges and limitations, the most appropriate strategies to fabricate efficient PSCs under ambient conditions are summarized along with multiple roadmaps to assist in the future development of this technology. Abstract : Although high‐efficiency perovskite solar cells (PSCs) are typically fabricated in a glovebox, strategies to fabricate PSCs in ambient conditions hold many advantages and are often overlooked. Importantly, high‐efficiency ambient PSCs can only be achieved if specific adaptations to their processing conditions are made. This review provides important design rules to fabricate efficient PSCs in ambient conditions.